High-throughput screening methods in toxicity testing - Steinberg, Pablo; Wiley eBooks (Hoboken, New Jersey : John Wiley & Sons Inc., 2013)
"High-throughput assays are part of a paradigm shift, to more cost-effective and reliable methods, in the testing of chemical and drug safety. This book covers methods, data generation, data analysis, and applications in risk assessment for major toxicological assays to help toxicologists apply and understand the benefits and limits of high-throughput testing assays. Each chapter describes method principles and includes detailed information on data generation, data analysis, and applications in risk assessment. The topic is especially timely given Europe's REACH legislation and the US National Research Council"--
"This book describes the high-throughput in vitro methods available for toxicity testing, serving as a guide to scientists working in toxicity evaluation and risk assessment of chemicals and drugs"--
pt. 1. General aspects -- pt. 2. High-throughput assays to assess different cytotoxicity endpoints -- pt. 3. High-throughput assays to assess DNA damage and carcinogenesis -- pt. 4. High-throughput assays to assess reproductive toxicity, cardiotoxicity, and haematotoxicity -- pt. 5. High-throughput assays to assess drug metabolism and receptor-related toxicity.
Includes index.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: High throughput screening (Drug development); Toxicity testing; SCIENCE -- Chemistry -- Industrial & Technical; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; High throughput screening (Drug development); Toxicity testing; Electronic books